Future direction of agrochemical development for plant disease in China - Guo, Shengxin; He, Feng; Song, Baoan; Wu, Jian (Food and energy security, 2021)
The growth of the global population poses a huge challenge to food security. The continuous application of crop protection products has many negative effects including increased pesticide resistance, accumulation of residues, and ecological damage. The challenge for the future is to develop agrochemicals with that are effective, with a high degree of selectivity, environmental friendliness, a low use rate, and cost‐effectiveness. Cutting‐edge developments in natural product chemistry, asymmetric synthesis, and rational drug design, as well as an increasing knowledge of the mechanisms that induce plant immunity, have provided potential solutions. In this review, we discuss the comprehensive use of emerging technologies that will help to tackle these current challenges and issues, highlighting the discovery of novel crop production products and their beneficial properties. Many complex and changeable factors including extreme climate, ecological deterioration, high agrochemical resistance and crop diseases from pests, weeds and pathogenic microorganisms have posed a great challenge for agriculture cultivation. Pesticides were used as the main measures to crop protection, and in this paper, we discuss the status and trends in the development of agrochemicals mainly from the perspective of microbicides, and the potential strategies that could be used as solutions for innovating agrochemicals.